Penyelesaian Perkara Harta Warisan dan Harta Bersama dengan Prosedur Mediasi di Pengadilan Agama Badung (Nomor Perkara 0095/PDTG/2017/PABDG) - I Kadek Leo Byasama Wijaya; I Nyoman Putu Budiartha; Ni Made Puspautari Ujianti (Warmadewa Press, 2021)
Disputes over joint property mixed with inheritance Dispute resolution specifically means that in a dispute that occurs between a husband and wife there is a difference of opinion between the two parties because property can also refer to a dispute So that for this there is an imbalance of ownership and a policy is needed to equalize the position of both parties Based on the background of the problems that have been described several problems can be formulated as follows 1) How is the Legal Power of mediation in the trial process at the Badung Religious Court? 2) What are the procedures for distributing inheritance and collective assets according to the compilation of Islamic law? This type of research used here is a type of empirical research where this research is carried out on the real situation in a community or the surrounding environment with the aim of finding facts or existing legal problems The results of this study indicate that the legal power of mediation in the trial process at the Badung Religious Court namely with the peace deed the results of the peace agreement get legal certainty